Exploring the impact of post-COVID-19 taste loss on food-related experiences, quality of life, coping strategies, and rehabilitation - Arumugam Vignesh; Thomas Cheeran Amal; Krishnan Vasanth (Discover Food)
Abstract The COVID-19 pandemic has significantly reshaped various aspects of daily life, including the way we perceive and experience food. This review explores the emerging issue of taste alterations among individuals recovering from COVID-19, focusing on the changes in taste preferences and the broader consequences for culinary experiences. It investigates the complex relationship between SARS-CoV-2 and the chemosensory systems, highlighting the physiological mechanisms that contribute to disturbances in taste and smell. Beyond individual sensory changes, the discussion expands to consider the impact on the food industry, culinary traditions, and social dining habits. Through addressing these evolving sensory experiences, the review emphasizes the need for greater awareness and adaptive strategies for those affected. It also offers valuable perspectives for researchers, clinicians, and food professionals aiming to support recovery and innovation in the post-pandemic culinary landscape. Ultimately, this examination contributes to a deeper understanding of COVID-19’s lasting influence on human taste and gastronomy.